2007
DOI: 10.1007/s00402-007-0526-1
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical and functional analysis of the pins and rubbers tractions system for treatment of proximal interphalangeal joint fracture dislocations

Abstract: The PRTS allows for efficient treatment of intraarticular fractures with PiP involvement. Although standardized positioning of the wires is important, proximal position of the retraction only increased forces for 30 degrees flexion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
3
8
1
2
Order By: Relevance
“…Even so, results in both these patients must be seen as failures of treatment. In the remaining 16 patients the final range of movement of the PIP joint was in the lower range of that reported by others who have published their results of Suzuki traction [2,4,6,[9][10][11].…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…Even so, results in both these patients must be seen as failures of treatment. In the remaining 16 patients the final range of movement of the PIP joint was in the lower range of that reported by others who have published their results of Suzuki traction [2,4,6,[9][10][11].…”
Section: Discussionsupporting
confidence: 40%
“…This may be the result of our extensive use of thick vessel loops instead of rubber bands. It has been shown [10] that five to 10 times the usual force is required to flex a PIP joint in traction with rubber bands. It may be that even more force is required when thick vessel loops are used, which are much less elastic, and perhaps our patients were unable to overcome this resistance to flexion.…”
Section: Discussionmentioning
confidence: 99%
“…Pin tract sepsis and osteolysis were never a problem, whereas such complications appear to be fairly frequent in other series [15,17,18] as evidenced by De Soras et al who reported five inflammations and one osteolysis out of a total of 11 cases [19]. This is probably due to the fact that in other series, the proximal pin was subjected to mechanical stress in rotation which is not the case in our series where the plastic spherical joints -and not the pins -absorbed the stress.…”
Section: Discussionmentioning
confidence: 94%
“…If we objectively analyse the quality of the frames, we can see that in eight cases of fracture of the middle phalanx, the traction pin was placed too proximally (Fig 1). It seems, however, that it could substantially increase the traction force of the flexor digitorum profundus tendon at 30 of flexion (Kneser et al, 2009). The issue here is not the force but the range of motion.…”
Section: Discussionmentioning
confidence: 95%